Village Information System Development For Data Sovereignty - Fadjarini Sulistyowati; Subejo Subejo; Muhamad Sulhan (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2025)
The development of the Village Information System (SID) mandated by Village Law No. 6 of 2014 is not merely a formality to fulfill obligations but its existence is crucial as documentation of village data consisting of population data, village potential and village programs. This can certainly occur if the village can interpret the data it has. The study aims to determine the development of SID and the use of data in development. The study used a descriptive analytical method, data collection techniques obtained from FGDs, interviews, observation and documentation. Data analysis used interactive analysis techniques. The results show that the Panggungharjo Village Government has developed SID independently with institutional support, funding, and professional human resources. SID supports more transparent administrative services, encouraging the emergence of various data-based public programs (scholarships and elderly assistance). These findings confirm that Panggungharjo has implemented the principle of data sovereignty, namely, the village has control over data and makes it the basis for development and public services.